Evaluation of three sorbent‐phase extraction techniques based on hyper‐crosslinked polymer for the extraction of five endocrine disrupters in water. Issue 3 (16th December 2021) - Huang, Guiqi; Su, Meiling; Zhang, Wei; Liu, Yamin; Chen, Chunyan; Li, Simin
Abstract: A series of low‐cost hyper‐crosslinked polymers were prepared by an easy one‐step Friedel‐Crafts reaction. The synthesized hyper‐crosslinked polymers exhibited remarkably porous structure, large surface area, and hydroxyl groups, which can be employed as an ideal adsorbent material for novel sorbent‐phase extraction techniques. Based on this, using hyper‐crosslinked polymers as sorbent and coating, three novel extraction methods, including micro‐solid‐phase extraction, dispersive solid‐phase extraction, and solid‐phase microextraction, were explored and evaluated for simultaneous measurement of five endocrine‐disrupting compounds (triclosan and bisphenol A, tetrabromobisphenol A, tetrabromobisphenol A bisallylether, and tetrabromobisphenol A bis(2, 3‐dibromopropyl ether)) in environment water prior to high‐performance liquid chromatography–ultraviolet. The influence of experimental parameters on three extraction techniques such as extraction time, the amount of hyper‐crosslinked polymers, extraction temperature, ionic strength, and desorption conditions were optimized. Three previously mentioned methods provided limits of detection ranging from 0.01 to 0.05 μg/L, and high recoveries (85–99%) with relative standard deviations of 1.7–5.6%. This study presented the merits and disadvantages of three proposed extraction methods and their potential for effective monitoring of hazardous pollutants in real water samples.